Dynamical evolution, transport and detection of minor bodies in the Solar System - Mendes, Luana Liberato [UNESP] (2023)
The Near-Earth Objects (NEOs) population is sustained by bodies coming from the main asteroid belt and outer regions of the Solar System. In this study, we revisit the dynamic evolution of the known NEO population using a sample of 985 large objects with diameters > 1km. N-body gravitational simulations for 100 million years track their transferences between regions, revealing their most common routes and fates. Objects transferred to orbits very close to the Sun are eliminated due to the thermal disruption effect, which is the most efficient NEO removal mechanism affecting 70% of the objects. Over half of the bodies are transferred to the Jupiter Family Comets (JFC) region, and an even larger percentage exits the Solar System through it. Frequent exchanges occur between NEO and Main Asteroid Belt (MAB) regions, with nearly 30% of the studied sample moving to MAB, but less than 1% remaining in it. Approximately 14% of the studied NEOs survive or collide with one of the terrestrial planets, while 10% can reach the Centaurs (CEN) region and remain inside of it for a significant time. Regarding the NEOs’ inclination, observations reveal significant deviations from near-planar orbits. To address this, we study their evolution and the impact of the orbital inclination in the NEOs’ lifetimes. We find that NEOs’ environment encourages an increase in orbital inclination, favouring long-lived NEOs with an intermediate orbital inclination of approximately 20◦ to 60◦. Additionally, we focus on the study of the objects that collided with the planets and find that the NEOs with intermediate orbital inclinations represent a constant risk of collisions for their regular number of impacts with the Earth and Venus, leading to a frequency of one impact of a km-size object each ∼0.22Myrs and ∼0.13Myrs, respectively. Furthermore, approximately 2.5% of the studied NEO population eventually became Vatiras (objects between Mercury and Venus), which indicates that a population of inner-Venus km-sized objects should exist and they might represent a significant risk of collisions with our planet. Turning attention to the binary asteroids, studies of such objects provide valuable insights into the collisional and dynamical evolution of minor planets. Therefore, we perform a dedicated period detection method based on astrometry using the Gaia DR3 data set, where we aim to reduce observational bias and discover new binary systems. A series of filterings and validations yielded a list of 67 binary candidates, awaiting confirmation through other observation techniques. These findings can contribute to a comprehensive understanding of minor body dynamics and physical properties, with implications for different topics in Solar System evolution studies.